2014
DOI: 10.1021/jp4107603
|View full text |Cite
|
Sign up to set email alerts
|

On Rates and Mechanisms of OH and O3 Reactions with Isoprene-Derived Hydroxy Nitrates

Abstract: Eight distinct hydroxy nitrates are stable products of the first step in the atmospheric oxidation of isoprene by OH. The subsequent chemical fate of these molecules affects global and regional production of ozone and aerosol as well as the location of nitrogen deposition. We synthesized and purified 3 of the 8 isoprene hydroxy nitrate isomers: (E/Z)-2-methyl-4-nitrooxybut-2-ene-1-ol and 3-methyl-2-nitrooxybut-3-ene-1-ol. Oxidation of these molecules by OH and ozone was studied using both chemical ionization m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
236
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 118 publications
(254 citation statements)
references
References 62 publications
12
236
6
Order By: Relevance
“…The photooxidation of IEPOX produces C 4 dihydroxy carbonyls (DHC 4 ), C 4 hydroxy dicarbonyls (HDC 4 ), HAC, formic acid, and other products (42,89). In NO-rich environments, the minor route of the OH-initiated reaction of isoprene produces ISOPN, which are subsequently oxidized to HAC, hydroxy nitrates with backbones of MACN and MVKN, and other products (54,90,91). The major route of the NOdominated OH-initiated reaction (not shown) produces carbonyls such as methacrolein, methyl vinyl ketone, and HAC, among other products.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The photooxidation of IEPOX produces C 4 dihydroxy carbonyls (DHC 4 ), C 4 hydroxy dicarbonyls (HDC 4 ), HAC, formic acid, and other products (42,89). In NO-rich environments, the minor route of the OH-initiated reaction of isoprene produces ISOPN, which are subsequently oxidized to HAC, hydroxy nitrates with backbones of MACN and MVKN, and other products (54,90,91). The major route of the NOdominated OH-initiated reaction (not shown) produces carbonyls such as methacrolein, methyl vinyl ketone, and HAC, among other products.…”
Section: Resultsmentioning
confidence: 99%
“…For unsaturated compounds like ISOPN, deposition may comprise a smaller fraction (<10%) of the daytime sink because its reaction with OH is fast (54). Thus, errors in representation of ISOPN dry deposition will have a much smaller effect on simulated ISOPN surface concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…The HRToF-CIMS was calibrated for three isomers of isoprene hydroxynitrate (C 5 H 9 NO 4 ) (20). The iodide-adduct ionization is most sensitive to polar organics with hydroxy groups (14), and the dominant ON signal in the particle phase observed during the SOAS was of highly oxygenated compounds.…”
Section: Methodsmentioning
confidence: 99%
“…In CheT2, the overall yield of NO x from ISON was increased, in line with recent measurements (Perring et al, 2009), by increasing the ISON photolysis rate and adding an ISON + OH → NO 2 reaction channel. O 3 initiated degradation of ISON was also added based on the evidence of Lockwood et al (2010) -it should be noted, however, that Lee et al (2014) found that Lockwood et al (2010) substantially overestimated the rate of this reaction. Secondly, CheT2 includes the formation of hydroperoxy-aldehydes (HPALDs) from ISO 2 and subsequent rapid release of OH (Peeters et al, 2009).…”
Section: Isoprene Chemical Mechanismsmentioning
confidence: 99%